1992
DOI: 10.1002/bmc.1130060311
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatography with chemiluminescence detection of methamphetamine and its related compounds using 4‐(N,N‐dimethylaminosulphonyl)‐7‐fluoro‐2,1,3‐benzoxadiazole

Abstract: A high performance liquid chromatographic assay of methamphetamine (MP) and its related compounds, i.e. ephedrine (EP), norephedrine (NE), p-hydroxymethamphetamine (p-HMP), p-hydroxyamphetamine (p-HAP) and amphetamine (AP), with peroxyoxalate chemiluminescence detection has been developed. 4-(N,N-Dimethylaminosulphonyl)-7-fluoro-2,1,3-benzoxadiazole (DBD-F) was used as a fluorescent labeling reagent. A mixture of hydrogen peroxide and bis[4-nitro-2-(3,6,9-trioxadecyloxycarbonyl)phenyl] oxalate in acetonitrile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…Utilizing dansyl chloride as a fluorescent reagent, MA and its five metabolites in urine were determined (Hayakawa et al, 1993). Other derivatization reagents for the simultaneous determination of MA and its metabolites in HPLC/CL and /FL include N-(4-aminobutyl)-Nethyl-isoluminol (Nakashima et al, 1991) and 4-(N,Ndimethylaminosulphonyl)-7-fluoro-2,1,3-benzoxadiazole (Nakashima et al, 1992;Sato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing dansyl chloride as a fluorescent reagent, MA and its five metabolites in urine were determined (Hayakawa et al, 1993). Other derivatization reagents for the simultaneous determination of MA and its metabolites in HPLC/CL and /FL include N-(4-aminobutyl)-Nethyl-isoluminol (Nakashima et al, 1991) and 4-(N,Ndimethylaminosulphonyl)-7-fluoro-2,1,3-benzoxadiazole (Nakashima et al, 1992;Sato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the former derivatization method, MA and its five metabolites in urine were separately determined (Hayakawa et al, 1993). N-(4-Aminobuty1)-N-ethyl-isoluminol (Nakashima et al, 1991) and 4-(NJV-dimethylaminosulphonyl)-7-fluoro-2,1,3-benzoxadiazole (Nakashima et al, 1992) were also used as other derivatization reagents for the simultaneous determination of MA and its metabolites. In this study, we applied the CL-HPLC method using dansyl derivatives for the sensitive determination of MA and AP in hair samples and confirmed that its sensitivity was higher than that of GCMS using selective ion monitoring (SIM).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It was applied to the ultra trace analysis of catecholamines 26 , amino acids [27][28][29][30] , steroids [31][32][33] and drugs. 3,[34][35][36][37][38][39][42][43][44][45][46] …”
Section: ·3 Development Of the Methodsmentioning
confidence: 99%